Pengendalian Waktu Pekerjaan Konstruksi Pembangunan RSUD Dr. Sobirin Kabupaten Musi Rawas: Analysis of Time Control for Construction Work for the Construction of Dr. RSUD. Sobirin, Musi Rawas Regency - Perri Putra (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This paper comprehensively examines time control in construction projects in Indonesia, with a specific focus on the development project of the Regional General Hospital (RSUD) Dr. Sobirin in Musi Rawas Regency, South Sumatra. Effective time control is a crucial factor in the success of construction projects, especially for healthcare infrastructure projects that have a direct impact on public services. This paper explores various time control methods and techniques, specific challenges in the context of hospital construction in regional areas, as well as strategies and solutions implemented. The case study of RSUD Dr. Sobirin is presented to provide practical insights into the implementation of time control in the real-world context of healthcare facility construction in Indonesia.